Creating interactive iBook for academic writing among undergraduate students in a Malaysian University - Asmawi, Adelina; Md Nor, Mariani; Daniel, Esther Gnanamalar Sarojini; Farid, Farah Diana (2015)
The purpose of this study was to investigate the challenges to learning about and conducting research in academic writing projects in the field of education and then to determine the types of content and design most suitable for a local interactive iBook on research in education. This research applied quantitative approach within two phases of ADDEI model: Needs Analysis and Design Development (Bichelmeyer, 2005). The researcher selected 20 undergraduate students in the field of education whom were doing their academic writing within the University of Malaya. The respondents completed two questionnaires; Needs Analysis and iBook questionnaires to identify the challenges to learning and conducting research, and also the types of content and design most preferred in a local interactive iBook. The results of the study indicated that reviewing literature review was the most significant challenge for students in conducting research in education. Another problem was to identify a research problem in their research area. Findings also indicated that students significantly preferred the iBook in facilitating their learning in conducting research. Results suggested that the content of the iBook needed to be in a graphic manner with a clean layout, visible font size and attractive colours. The most preferred design of the iBook is keynotes with animation to convey content that are generally difficult to understand only through text. The aid of scrolling sidebar was found very effective when used in combination with video clips and interactive images in comprehension exercises for the learning process.